PENEGAKAN KODE ETIK WORLD HEALTH ORGANIZATION (WHO) DALAM PROMOSI DAN PENJUALAN SUSU FORMULA OLEH ASOSIASI PERUSAHAAN PRODUK BERNUTRISI UNTUK IBU DAN ANAK (APPNIA) TERKAIT PROGRAM PEMBERIAN AIR SUSU IBU (ASI) EKSKLUSIF (STUDI DI PT SARI HUSADA MALANG DAN DI SUPERMARKET KOTA MALANG) - Feby Kusumawardhani; Fatkhurohman Fatkhurohman; Sirajuddin Sirajuddin (Legal Spirit, 2017)
Breast milk is the best nutrition for infants. Exclusive breastfeeding may help reduce the risk of death in infants. In fact, many people are not aware of the benefits of breastfeeding.This is compounded by the incessant promotion of infant formula is as if the function can replace breast milk. To prevent excessive promotion of infant formula, WHO made WHO Code which forbade the activity of promotion of infant formula in order to ensure the fulfillment of breast milk for babies and supervise the use of breast milk substitute products. WHO Ethical Code was adopted in some regulations in Indonesia which is equipped with a reporting mechanism for those who violate them and the imposition of sanctions for such violations. WHO Ethical Code violations most often done by infant formula companies. In addition it can be reported through government channels, WHO Code violations committed by the infant formula companies also can be handled directly by APPNIA which is an association that is followed by all infant formula companies in Indonesia serving to enforce the rules of WHO Ethical Code. Key words: Code of ethics, Law enforcement, Exclusive breastfeeding program